Association between asthma with dry eye disease: A protocol for systematic review and meta-analysis. Issue 41 (9th October 2020) - Huang, Qun; Yang, Yang; Liao, Tingting; Zhang, Chuantao; Zheng, Yanlin; Wang, Wanjie; Xiao, Xili; Wang, Jing; Wang, Juan
Abstract: Backgoun: Asthma and dry eye disease are common clinical diseases. Studies have shown that asthma is related to dry eye, but there is no high-quality evidence-based medical evidence. Method: This protocol and final study will be conducted in accordance with the Preferred Reporting Items for Systematic review and Meta-Analysis Protocols 2015 statement. We will search PubMed, EMBASE, ISI Web of Science, China National Knowledge Infrastructure for all relevant literature published from their inception up to August 1, 2020. Literature search, data extraction, and quality assessment will be carried out independently by two researchers, and a third researcher will resolve differences when necessary. The association between dry eye disease and asthma will indicate as odds ratio with 95% confidence interval and statistically analyzed using RevMan 5.3 software. If the studies included have high heterogeneity, we will conduct sensitivity analysis and subgroup analysis. Results: The protocol is intended to guide a meta-analysis aimed at identifying and quantifying the association between asthma and dry eye disease.